Prolongation of atrio-ventricular node conduction in a rabbit model of ischaemic cardiomyopathy: Role of fibrosis and connexin remodelling. (May 2016) - Nisbet, Ashley M.; Camelliti, Patrizia; Walker, Nicola L.; Burton, Francis L.; Cobbe, Stuart M.; Kohl, Peter; Smith, Godfrey L.
Abstract: Conduction abnormalities are frequently associated with cardiac disease, though the mechanisms underlying the commonly associated increases in PQ interval are not known. This study uses a chronic left ventricular (LV) apex myocardial infarction (MI) model in the rabbit to create significant left ventricular dysfunction (LVD) 8 weeks post-MI. In vivo studies established that the PQ interval increases by approximately 7 ms (10%) with no significant change in average heart rate. Optical mapping of isolated Langendorff perfused rabbit hearts recapitulated this result: time to earliest activation of the LV was increased by 14 ms (16%) in the LVD group. Intra-atrial and LV transmural conduction times were not altered in the LVD group. Isolated AVN preparations from the LVD group demonstrated a significantly longer conduction time (by approximately 20 ms) between atrial and His electrograms than sham controls across a range of pacing cycle lengths. This difference was accompanied by increased effective refractory period and Wenckebach cycle length, suggesting significantly altered AVN electrophysiology post-MI. The AVN origin of abnormality was further highlighted by optical mapping of the isolated AVN. Immunohistochemistry of AVN preparations revealed increased fibrosis and gap junction protein (connexin43 and 40) remodelling in the AVN of LVD animals compared to sham. A significant increase in myocyte–non-myocyte connexin co-localization was also observed after LVD. These changes may increase the electrotonic load experienced by AVN muscle cells and contribute to slowed conduction velocity within the AVN. Highlights: Chronic myocardial infarction (MI) causes changes in atrio-ventricular node (AVN) function. Isolated hearts post-MI show delays in ventricular activation due to slowed conduction via the AVN. Isolated AVN preparations demonstrated AVN electrical remodelling post-MI. Electrical remodelling is associated with fibrosis and altered expression of connexins in the AVN. AVN dysfunction post-MI is caused by localized functional and structural remodelling.